Meeting the Millennium Development Goals with agricultural biodiversity - International Plant Genetic Resources Institute (2005)
In September 2005 the United Nations General Assembly will review progress towards the achievement of the Millennium Development Goals (MDGs). This will be an important opportunity to enhance understanding of the contributions that plant diversity can make to improve the livelihoods of poor people.. The International Plant Genetic Resources Institute, the Global Facilitation Unit for Underutilized Species and the M.S. Swaminathan Research Foundation, with the support of sponsors, organized an international consultation meeting in Chennai, India, in April 2005 to examine the value of agricultural biodiversity in meeting the MDGs. The meeting set out to underscore the contribution that agricultural biodiversity makes to improving livelihoods. It also addressed policies, institutional constraints and other issues that challenge the full deployment of biodiversity and hence limit the achievement of the MDGs. By doing so, it sought to draw greater attention and commitment from policy-makers and the donor community. One outcome of the meeting is an action plan to promote local, community-centred systems that will deliver improved food security and health, based on the cultivation of a wide range of food crops, vegetables, fruits and medicinal plants. We hope that this action plan will be widely adopted, because the eradication of hunger and poverty must become an overriding priority for public action and investment. Every child, woman and man should have the opportunity for a productive and healthy life. This will be possible only if we integrate cutting-edge science and technology with dying wisdom and vanishing crops.